Synthesis and Applications in Chemistry and Materials (ed. A. J. L. Pombeiro, K. T. Mahmudov and M. F. C. Guedes da Silva), Series on Chemistry, Energy and the Environment, vol. 11–14, World Scientific Publishing (March 2024): a review - Braunstein, Pierre (Comptes Rendus. Chimie)
Critical review of four new volumes in the book series “Series on Chemistry, Energy and the Environment” (World Scientific Publishing, Singapore): Synthesis and Applications in Chemistry and Materials, 4 volumes, 2100 pages (March 2024). https://doi.org/10.1142/13309.Volume 11: Metal Coordination and NanomaterialsVolume 12: Enzymatic and Organic SystemsVolume 13: Metal Complex Catalytic Systems and MaterialsVolume 14: Biomass and Waste Valorisation, Functional Materials, Energy Conversion and Supercritical SystemsThese volumes were edited by Armando J. L. Pombeiro (Universidade de Lisboa, Portugal), Kamran T. Mahmudov (Universidade de Lisboa, Portugal) and M. Fátima C. Guedes da Silva (Universidade de Lisboa, Portugal).